Ghost Passenger in the Heart: The Story of an Intracardiac Cyst Dancing with Coronary and Peripheral Embolisms - Aydın, Nergiz; Sertdemir, Ahmet Lütfü; Alsancak, Yakup (European Journal of Therapeutics, 2024)
Cardiac localization of hydatid cyst, which is a parasitic disease, is rare. In this article, a case of mediastinal hydatid cyst invading the left atrium is presented. A 62-year-old male patient with risk factors for coronary artery disease presented with epigatric pain, nausea and vomiting. Coronary imaging was performed because ongoing epigatric pain was accompanied by ischemic changes and elevated troponin on electrocardiography. No occlusive lesion was observed in the epicardial coronary arteries. Mesenteric embolism was detected in the patient whose epigatric pain continued. The patient, who did not accept surgery after the initial diagnosis, developed peripheral and cerebral emboli in the following period, and the patient was referred for surgery.